Development of a Customer Behavior Data Analysis System to Support Online Business Planning - ภักดี, กรภัทร์; วุฒิกร, ช่อผกา ว; ไชติคะ, ธนกฤต; พุทธินันท์ นาคสุข, พุทธินันท์ นาคสุข (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
The research entitled “Development of a Customer Behavior Analysis System to Support Online Business Planning” aimed to: 1) develop a customer behavior analysis system to support online business planning, and 2) study users’ satisfaction with the use of the customer behavior analysis system for online business planning.            The sample group used in this study consisted of 30 social media users who had experience in online shopping and were convenient to respond to an online questionnaire. The samples were selected by purposive sampling. The research instruments included: 1) a customer behavior analysis system to support online business planning, 2) an efficiency evaluation form completed by experts, and 3) a user satisfaction questionnaire regarding the use of the customer behavior analysis system to support online business planning.            The results of the study revealed that the developed customer behavior analysis system was efficient according to the expert evaluation. Descriptive statistics were used for data analysis, including the mean and standard deviation. The expert evaluation showed an average score (x̄) of 4.35 with a standard deviation (S.D.) of 0.40. In addition, the satisfaction of users toward the customer behavior analysis system showed a mean score (x̄) of 4.46 with a standard deviation (S.D.) of 0.50. It can be concluded that the developed customer behavior analysis system was effective in analyzing customer behavior data and could be applied to business planning in a way that was well aligned with consumer needs.